2019
DOI: 10.1016/j.cmet.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis Reveals AMPK Is Required to Support Tumor Growth in Murine Kras-Dependent Lung Cancer Models

Abstract: Highlights d AMPK does not phenocopy the lung tumor-suppressor role of its activator LKB1 d AMPK deletion reduces tumor burden in KrasG12D and Kras p53 À/À lung cancer models d AMPK is required during glucose deprivation to induce Tfeb and Tfe3 activation d Tfe3 activity is required for growth of mouse lung tumors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
153
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 51 publications
10
153
0
1
Order By: Relevance
“…Cancer cells must adapt to metabolic stress during tumor progression. In this issue of Cell Metabolism, Eichner et al (2019) report that lung cancer development in genetically engineered mice requires the energy sensor AMP-activated protein kinase (AMPK). Their findings suggest that AMPK-mediated induction of lysosomal function supports cancer cell fitness, particularly during the early stages of tumorigenesis.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Cancer cells must adapt to metabolic stress during tumor progression. In this issue of Cell Metabolism, Eichner et al (2019) report that lung cancer development in genetically engineered mice requires the energy sensor AMP-activated protein kinase (AMPK). Their findings suggest that AMPK-mediated induction of lysosomal function supports cancer cell fitness, particularly during the early stages of tumorigenesis.…”
mentioning
confidence: 99%
“…By contrast, studies using cancer cell lines and transformed primary cells have shown that AMPK deficiency leads to metabolic defects that attenuate malignant growth (Chhipa et al, 2018;Jeon et al, 2012;Laderoute et al, 2006;Saito et al, 2015). In this issue of Cell Metabolism, Eichner and colleagues address this question in the context of the initiation and progression of tumors arising from normal cells in their native tissue setting using genetically engineered mouse models (GEMMs) (Eichner et al, 2019). Eichner et al (2019) focused on lung cancer, a malignancy in which LKB1/ STK11 loss-of-function mutations are common and frequently co-exist with KRAS-activating mutations.…”
mentioning
confidence: 99%
See 3 more Smart Citations